Influencia de la actividad física en la enfermedad de Alzheimer: un caso clínico - Christofoletti, G.; Oliani, M. M.; Corazza, D. I. [UNESP]; Stella, F. [UNESP]; Gobbi, S. [UNESP]; Bucken-Gobbi, L. T. [UNESP]; Borges, G. (Elsevier, 2009)
Alzheimer's dementia (AD) is a neurodegenerative disorder that causes motor and cognitive decline. The aim of this study was to analyze the influence of a specific physical activity program on the cognitive, depressive symptoms and functional capacity of patients with diagnosis of probable AD. The subject, a 79-year old woman, participated in this program for three months, with 50 min sessions three times a week. The instruments used were the Cambridge Cognitive Examination; the Geriatric Depression Scale; and the Battery of the American Alliance for Health Physical Education, Recreation and Dance. The results in relationship with the depressive symptoms and functional capacity were significantly positive. There were no changes in regards to the patient's cognitive functions. In conclusion, this physical activity program seems to be an important part of the treatment for patients with AD, as it improves the functional capacity and also stimulates cognitive tasks. © 2008 Asociación Española de Fisioterapeutas.
Influence of physical activity in Alzheimer's disease: A clinical case
Keywords: Alzheimer's dementia; Cognitive functions; Functional capacity; Physical activity